Applying the Zachman Framework to Enterprise Architecture: A Multi-View Perspective on Business–IT Alignment in Platform-Based Firms - Andika Isma; Alfian Pasomba; Andi Naila Quin Azisah Alisyahbana (Indonesian Journal of Enterprise Architecture, 2025)
PT. Dekoruma Inovasi Lestari (Dekoruma) is a technology-based company, which focuses on furniture sales, interior design services, and property sales. The company's extensive business lines require more comprehensive data and applications than currently available. Therefore, an enterprise architecture design is needed for this company so that all business lines can run smoothly. This study aims to design the Dekoruma company's enterprise architecture. This study uses an enterprise architecture planning method with the Zachman framework approach. The focus of this study lies in four important aspects of the Zachman framework, namely scope, business model, system model, and technology model, as well as two main components in the Zachman framework, namely the data column (what) and the function column (how). The result of this study is an initial enterprise architecture design that describes the data and application requirements that can be implemented. In addition, this study also produces a list of application recommendations and implementation plans that can be implemented.